PENGARUH SUDUT PENYAYATAN DAN JUMLAH MATA SAYAT ENDMILL CUTTER TERHADAP TINGKAT KEKASARAN PERMUKAAN BAJA ST 40 HASIL PEMESINAN CNC MILLING TOSURO KONTROL GSK 983 MA-H - Zainuddin, Zainuddin (Jurnal Nosel, 2013)
The purpose of this study is to determine: (1) the effect of endmill cutter primary angel to the roughness level of steel ST 40 machining result by Tosuro CNC Milling controlled by GSK 983 Ma-H. (2) The effect of the endmill cutter flute amount to the roughness level of steel ST 40 machining result by Tosuro CNC Milling controlled by GSK 983 Ma-H. (3) a combination of primary angel and the flute amount of endmill cutter which produces the smallest level of roughness. This study is an experiment that uses two-factor variables (angle incision and the number of eyes slice endmill cutter) and one dependent variable (the level of surface roughness). This study was conducted at the Machining Practices Laboratory of SMK Warga Surakarta for the formation of Test Objects and implementation of the machining process using Tosuro CNC Milling controlled by GSK Ma-H. The level of the surface roughness conducted at Engineering Materials Laboratory of Mechanical Engineering Diploma, The Faculty of Engineering, GadjahMada University. The research method used in this study is an experimental method with analytic descriptive analytical techniques. The results showed that there was primary angel and the flute amount of endmill cutter effect to the roughness level of steel ST 40 machining result by Tosuro CNC Milling controlled by GSK 983 Ma-H. The smallest combination of primary angel and the flute amount of endmill cutter toward the roughness level of steel ST 40 machining results process by TS 218 CNC Milling is on the interaction between primary angel of 5° and 4 flutes of  endmill cutter is equal to 0,2013 µm and the greatest of the roughness level of steel ST 40 machining results process by TS 218 CNC Milling is on the interaction between primary angel of 10° and 2 flutes of endmill cutter is equal to 0,4691 µm. The more the amount of endmill cutter the smaller the level of the roughness.